EFEKTIFITAS PELATIHAN DALAM MENINGKATKAN KINERJA KARYAWAN (STUDI KASUS PADA PT. BANYUMAS RAYA TRANSPORTASI) - Inayah, Anisa Afri; Hermaliawati, Lezyana; Fitricia, Grace Maria; Yuttama, Faizal Rizky; Kurniawan, April (Bisnis-Net, 2025)
This research aims to analyze the effectiveness of training in improving employee performance at PT. Banyumas Raya Transportation. Competent and skilled human resources are very important in achieving company goals, especially in an era of intense competition. Training is one of the main strategies to improve employee skills and knowledge. The research method used is descriptive qualitative with a case study approach, which involves interviews with HRD and documentation in the form of recordings related to training that has been carried out over the last three years. The research results show that the training carried out is more focused on drivers, while employees in other divisions have not received specific training. Even though training provides insight and knowledge, its effectiveness is still less than optimal because it does not involve all divisions as a whole. This research aims to ensure that companies provide more targeted training for all divisions, as well as carry out regular evaluations of the training programs that have been implemented. So, it is hoped that employee performance can increase significantly